SARS-COV-2 viroporins activate the NLRP3-inflammasome by the mitochondrial permeability transition pore - Guarnieri, Joseph W.; Angelin, Alessia; Murdock, Deborah G.; Schaefer, Patrick; Portluri, Prasanth; Lie, Timothy; Huang, Jessica; Wallace, Douglas C. (Frontiers in Immunology, 2023)
Cytokine storm is a major cause of COVID19 death. To elucidate how SARS-CoV2 initiates this inflammatory process, we studied viroporin proteins E and Orf3a (2-E+2-3a). Expression of 2-E+2-3a in 293T cells increased cytosolic Ca++ and elevated mitochondrial Ca++, taken up through the MCUi11-sensitive mitochondrial calcium uniporter. Increased mitochondrial Ca++ stimulated NADH and mitochondrial reactive oxygen species (mROS) production, which was blocked by mitochondrially-targeted catalase or MnTBAP. To determined how mROS activates the inflammasome, we reconstituted the mitochondrially-bound NLRP3-inflammasome in 293T cells and used THP1 derived macrophages to monitor the secretion of mature interleukin (IL)-1β. This revealed that mROS activates the release of mitochondrial DNA via the NIM811-sensitive mitochondrial permeability pore (mtPTP), activating the inflammasome. Hence, interventions targeting mROS and the mtPTP may mitigate the severity of COVID19 cytokine storms.